Optimizing The Role and Function of Law to Protect PT Krakatau Steel (Persero), Tbk & Group Business Interests from The Human Capital and Organization Perspectives - Budiman, Iip Arief; Saksono, Prasetyo Budi (The Indonesian Journal of Business Administration, 2014)
Abstract. After the reform era in 1999, PT Krakatau Steel (Persero), Tbk has faced many international and domestic legal challenges and issues in running its business, such as antidumping lawsuit, international contract for main raw materials transaction, filing a lawsuit to a company in Australia, many lawsuits in the homeland court and arbitration, and obligation to more comply all law and regulations after made in Initial Public Offering in November 2010. The above mentioned legal issues as well as other routine work that pertain to initiate legal documents, license handling, mentoring of the employee and official of the Company who is summoned by the authorities, both in the holding Company and subsidiaries (PT Krakatau Steel (Persero), Tbk and Group) are all handled by an organizational unit namely the Division of Legal Office. The increasing complexity of the problems faced by the Company, particularly the legal issues, become the obstacle of company’s business activities so that it can hinder to the implementation of good corporate governance. In order to deal with the complex legal issues and demands the implementation of GCG that can be effectively run, the Legal Division Office should be encouraged to improve the implementation of its function and its role in protecting the business interests of the Company. Those matters increase the demand for legal experts who have high competence and professionalism in carrying out their tasks and functions. In order to support the above needs, it is proposesd that the organization of Legal Office Division to be divided  into 3 (three) group of expertise:(a) Legal for Commercial & Business Transaction Group; (b) Legal for Corporate Affairs, Claim & Litigation Group; and (c) Legal for Compliance & Subsidiary Affairs Group. At the same time, the number of legal personnel should also be added by placing its subsidiaries legal personnel in the corporate level. Keywords : Legal problems, organization of legal office division, specialized, group of expertise, and protecting the Company’s business interest.